MindSight: A Bio-Inspired Neural Architecture for Visual Restoration via Cortical Electrical Stimulation - Zou, Yongjie; Niu, Haonan; Zhao, Bin; Yi, Guoliang; Yang, Mengchuanzhi; Ju, Jiawei; Yin, Jiapeng; Li, Chengyu T. (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Visual impairment is a common condition worldwide, and cortical electrical stimulation is one of the approaches to aid in visual restoration. However, existing methods suffer from limited precision, flexibility, and generalization in generating the desired visual perception. In this paper, we propose a novel deep learning-based algorithm for cortical electrical stimulation, named ``MindSight," aimed at enhancing the clarity and accuracy of induced visual perceptions. Our framework introduces three key innovations: (1) A differentiable biophysical model simulating cortical state transitions under electrical stimulation, enabling end-to-end training; (2) A dual-path training architecture combining neural decoding fidelity with phosphene simulation constraints; (3) An attention-guided background gated network for input filtration and, a multi-channel activation constraint to ensure the effectiveness of electrical stimulation. We validated our approach through novel experiments with macaque monkeys, demonstrating superior performance in visual perception tasks. These results highlight the potential of our approach in assisting individuals with visual impairments.